Anishnabeg children and youth's experiences and understandings of oral health in rural Quebec - Ye Na Kim; Louise-Esther Bond Rouleau; Franco Carnevale; Georgina Whiteduck; Denise Chief; Mary Ellen Macdonald (James Cook University, 2021)
Introduction: Children's oral health is a prevalent health concern in Indigenous communities in Canada and globally. Compared to an early childhood caries prevalence rate of 57% in non-Indigenous Canadian school-age children, some Indigenous communities face rates exceeding 90%. Despite the high prevalence rates of caries and other oral health concerns in Indigenous children, qualitative research on oral health has focused on Indigenous adults. This study sought to uncover children and youths' oral health experiences and understandings in two Anishnabeg communities in Quebec. Methods: A focused ethnography was conducted using participatory research principles, and included interviews with key informants, children, and youth, as well as participant observation of oral health activities. Analysis was iterative and concurrent with data collection. Results: Themes include (1) children and youth primarily described oral health in relation to their teeth only; (2) children and youth have motivators for maintaining oral health, including consequences of poor oral health and its influence on self-presentation; (3) oral health is 'put on the side table', and not highly prioritized by children or adults; (4) children and youth recognize the people in their lives that influence their oral health; and (5) children and youth demonstrate agency in oral health matters. Conclusion: These results demonstrate the valuable perspectives that Anishnabeg children and youth have regarding their oral health, and are of value to other Indigenous communities that strive to address similar oral health concerns.